ANALISIS JANGKAUAN PELAYANAN LOKASI MINIMARKET DI KECAMATAN GUNUNGPATI KOTA SEMARANG - Kurniawan, Wisnu; Suroso, Suroso; Tjahjono, Heri (Geo-Image, 2016)
This study is based on the development of the mini region of the District Gunungpati uneven in its establishment. The total population of 75.910 inhabitants as consumers are scattered in 16 villages by the number of minimarkets many as 17 units, then on average each serve about 4,743 inhabitants minimarket.This study aimed: Knowing the level of suitability minimarket in Gunungpati sub-district. This research method is descriptive qualitative. Data analysis technique in this research is the analysis of data comparations. The object of this research is minimarkets in Gunungpati sub-district and traditional markets in Gunungpati. Data used include primary data questionnaires and surveys using GPS, while secondary data is the Gunungpati sub-district In Figures 2014, the data population, data on the number minimarket and data description of the area.The number of samples that are in two regions Gunungpati village and Sadeng village, with 40 respondents, ie 40 minimarket visitors taken from the questionnaire to Gunungpati sub-district’s resident.The results showed concordance rate in Gunungpati village categorized low with a score of 13, while for the Sadeng village also categorized low with a score of 14. Coverage area minimarket locations in the sub-district Gunungpati largely overlapping or overlapping with a minimum distance of 500 meters between a minimarket to the other minimarket. Establishment location minimarket adjusted with applicable government regulations that competition in the world economy is getting healthier and range of services do not overlap.